Hubungan Pola Asuh Orang Tua dengan Perkembangan Anak Usia 4-6 tahun di TK Al-Faridah Kecamatan Sindangkasih Kabupaten Ciamis Tahun 2014 - Yati Budiarti; Sri Gustini; Siti Saadah; Endang Astiriyani (STIKes Persada Husada Indonesia, 2015)
Quality of child is determinant of human resources in the future. Therefore children coaching need tobegin in the early age to prepare for qualified human resources. Key to the success of a child to becomeindependent are affected by several factors, one of which is the parent parenting pattern. Therefore it is theparents who play a role innurturing, guiding and helping direct the child to become independent. The purpose ofthis study is to determine the relationship of parenting parents pattern with child development ages 4-6 years Al-Faridah Kindergarten. Traditional survey research methods were used with analytic cross-sectional approach.The population of entire kindergarten students at Al-Faridah ages 4-6years and their parents with the total 46respondents. Sampling technique used saturated sampling technique. The results showed the majority of parentsuse authoritative parenting (58,7%), appropriate child development (30,4%), deviation and doubt (34,8%). Pvalue obtained was 0,022 showed there area relationship between parenting parents with child development.Research result summarized a significant relationship exists between parenting parents pattern with childdevelopmentages 4-6years at kindergarten Al-Faridah.Keywords: patterns of parenting, child development ages4-6 years.